Improvement of distributed timestamp synchronization - Kai LIN; Chun-fu JIA; Le-yi SHI (Tongxin xuebao)
Distributed timestamp synchronization (DTS) could satisfy the requirement of synchronization for end hopping,but still had some degree failure of synchronization.An improved scheme of DTS(say IDTS)was proposed by providing two additional endpoints to receive the unsynchronized packets.It established models and definitions for end hopping system at first,then provided protocol for IDTS，analyzed the effectiveness and security of IDTS.Finally,the empirical results show the practical value of IDTS.